ALL-RUSSIAN THEORETICAL AND PRACTICAL CONFERENCE «PHARMACOTHERAPY AND DIETETICS IN PEDIATRICS» DEDICATED TO THE 250th ANNIVERSARY OF THE STATE SYSTEM OF CHILDREN'S HEALTH PROTECTION IN RUSSIA AND OF THE SCIENTIFIC CENTER OF CHILDREN'S HEALTH - article Editorial (Union of pediatricians of Russia, 2013)
.